2010
DOI: 10.1111/j.1439-0418.2009.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pymetrozine against Myzus persicae and in reducing potato virus Y transmission on tobacco plants

Abstract: Forty‐four parthenogenetic lineages of Myzus persicae s.l. (Sulzer) from tobacco crops and peach orchards located in various regions of Greece were examined to determine their response to the insecticide pymetrozine using leaf‐dip bio‐assays. The results show that the aphid has not developed resistance, as all lineages exhibited resistance factors bellow 6.0. In transmission experiments of potato virus Y (PVY) using a lineage of the tobacco‐adapted subspecies M. persicae nicotianae Blackman on tobacco plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…A similar protective effect of mineral oils in suppressing the transmission of different viruses was reported by a number of researchers [POWELL et al, 1998;MARGARITOPOULOS et al, 2009;SURANYI, 2010] .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…A similar protective effect of mineral oils in suppressing the transmission of different viruses was reported by a number of researchers [POWELL et al, 1998;MARGARITOPOULOS et al, 2009;SURANYI, 2010] .…”
Section: Resultssupporting
confidence: 74%
“…In addition to the positive manifestations of mineral oils, there were studies which have established a synergistic effect when combining mineral oils with insecticides [AL-MRABEH et al, 2010] , protection of plants from different viruses by suppressing their transmission [POWELL et al, 1998;SURANYI, 2010;MARGARITOPOULOS et al, 2009] and lower toxicity of the oils in regard to the beneficial entomofauna compared with other pesticides [MCLAREN et al, 2008] .…”
Section: Methodsmentioning
confidence: 99%
“…This way both insecticide groups may continue being effective for longer. In addition, pymetrozine, a pyridine azomethine, which causes irreversible cessation of feeding, could be used as another alternative to neonicotinoids as it has a completely different MoA (IRAC MoA group 9B) and there have been no reports of resistance in Greek and European populations of M. persicae . In crops that suffer from aphid‐transmitted plant‐viruses pymetrozine could be a valuable alternative, as it significantly reduces virus transmission …”
Section: Discussionmentioning
confidence: 99%
“…The inoculation of non‐persistent viruses is associated with salivation during brief cell punctures by the stylets while that of persistent viruses is thought to occur during phloem salivation . Previous studies have often shown the application of insecticides to be beneficial in reducing the spread of plant viruses . From this study it appears that M. persicae disperses at the same rate regardless of the presence or absence of neonicotinoid treatment, hence in theory, the application of neonicotinoids should exert either a beneficial (due to increased vector mortality) or else no effect on the rates at which plant viruses spread within a crop, supporting such findings.…”
Section: Discussionmentioning
confidence: 63%